Enhancing curriculum development: a comprehensive framework for undergraduate competencies - Alvarez, Ma Teresa Silos; Guinat, Sheila Y. (Institute of Advanced Engineering and Science, 2025)
In the context of significant changes in higher education and the job market, there has been extensive discussion on what qualifies graduate competency and what shapes graduates’ labor market outcomes. Each university’s vision is to produce highly competitive and educated graduates with high competence and contribute to the country’s development. Graduate employability is a key issue for higher education. Ensuring their competency is vital in forming an educated graduate the industry is looking for. Their competency is honed based on the activities and curriculum of the program as embedded in the circular memorandum order (CMO) of each program. A descriptive research design was used and a questionnaire on structured institutionalized tracer instrument and CMO 17 s.2017 was adopted. Uses statistical treatment such as mean, frequency, percentages and t-tests. This study focuses to assess and evaluate the competency of our graduates in response to the needs of the industry and for curriculum enhancement. The results reveal that the bachelor of science in business administration (BSBA) graduate’s competency based on all the identified parameters was deemed